VD_FINDINFO HC / 2012 / 561 vom 4. Juli 2012 - VD Tribunal cantonal (2012)
OBLIGATION D'ENTRETIEN, ENFANT, MINIMUM VITAL, MODIFICATIONEN GÉNÉRAL, DIVORCE | 134 al. 2 CC, 286 al. 2 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 405 al. 1 CPC (CH)